Dental Student Perspectives of a Comprehensive-Based Teaching Methodology: A Confidence, Effectiveness, and Challenge Report - Susan Hattar; Abeer AlHadidi; Sandra Altarawneh; Suha Abu-Ghazaleh; Mohammad Hammad (Hindawi Limited, 2020)
Background/Objectives. The holistic methodology in education has been widely appreciated and implicated in dental schools in the last decade. Our department of conservative dentistry decided to reform the educational model of teaching from a traditional requirement-based model to a hybrid model incorporating comprehensive care treatment. The aim of our study was to assess students' confidence and perspectives regarding the benefits of a comprehensive model of teaching. Materials and Methods. A questionnaire was distributed at the end of the academic year 2018-2019 and designed to investigate students' opinions on the benefits of the new model of teaching, as well as difficulties encountered and possible shortcomings. In addition, self-perceived confidence level was assessed for the purpose of comparing confidence during supervised tasks versus confidence during comprehensive patient care. Results. Complete responses were gathered from 127 students out of 202, giving a response rate of 63%. The majority of students believed that the comprehensive model of teaching allowed them to better address patients' needs, gave higher satisfaction, positively influenced self-confidence, permitted greater exposure to clinical techniques, and enhanced reasoning and analytical skills. However, their confidence was still lower in comprehensive patient management when compared to supervised tasks. Conclusion. Our students showed an appreciation of the comprehensive care model. Self-learning and didactic skills were enhanced. It would, therefore, be beneficial to adapt this methodology to earlier years and other disciplines to enhance the effectiveness of education and achievement of learning outcomes.